Taṭwīr Mawād at-Tarākīb Fī Kitāb al-Lughah al-`Arabiyah al-Madrasī Kurikulum 2013 Bi Microsoft Powerpoint - Raudhatul Jannah; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
The title of this research is the Development of Material structure in Arabic Textbook 2013 Curriculum year, with Microsoft Powerpoint. The researcher choises this title because she saw as who the students of SMP Muhammadiyah 1 Banda Aceh, in practicing Arabic they did not pay attention to the correct language principles. Especially when they practiced Arabic sentences do not match verb and personal pronound be right. Were in this school the students really like learning by using media, this fhenomenals can be seen from the student questionnaire that they were very enthusiastic about learning by using Powerpoint. Therefore, the researcher wants to develop structural material using Powerpoint. The purpose of this research is to develop a product for the development of material structural and to determine the effectiveness of the material by using Power point, and to find out what the experts think about the development of by material structural using Powerpoint media. For data collection, the researcher used a pretest and postest question questionnaire and an expert observation sheet. The results of the research are that the use of Microsoft Powerpoint media in developing the material structure increases student ability in learning structure, so that the media is effective for teachers in increasing ability to learn it. Based on the results of the posttest average score (T-test 2,09 <7,1> 2,86.) this value shows that the development of material structure by using Powerpoint media at SMP Muhammadiyah 1 Banda Aceh is effective and useful. As for the expert assessment, it shows that the product is accepted based on the expert observation value, namely 80% from expert I, and 75% from expert II